Synthetic power grid development: optimal power system planning-based approach and its application for Singapore case study - Trpovski, Andrej (Nanyang Technological University, 2024)
To cope with the progressive challenges imposed by recent technological advancements in the power and energy sector, it is essential to modernize the power systems into 'smarter' and more resilient grids. Strict environmental and sustainability objectives have accelerated the development of renewable energy (RE), distributed energy resources (DER), battery energy storage systems (BESS), electric vehicles (EVs) and information and communication technologies (ICT). The loads are defined as flexible and controllable, the consumers become prosumers, the energy mix is changing, new programs such as demand response are continuously explored and introduced, and the energy markets transition to a deregulated market environment. These developments give way for new concepts and opportunities and introduce many new stakeholders that change the grid landscape. Despite the numerous potential benefits offered with such advancements, there is a necessity to analyze the impact on the grid and identify the associated challenges. The above-mentioned technologies and developments will have an effect on the power system which needs to be analyzed in details. These developments are just adding further pressure on utilities to reach the modern grid objectives, with minimal investment cost, without putting at risk the critical services they currently provide. Considering the importance of the power system as an essential facility, providing an uninterrupted service is the primary concern for a real-life implementation. However, it has been acknowledged that the absence of near-real world research, development and demonstration (RD&D) capabilities are challenges that power industry players need to overcome to enable the development, validation, and help qualify technologies, applications, and solutions as part of the smart grid initiative. However, detailed real power system models are classified as critical infrastructure of high priority with confidentiality restrictions. Such information is not publicly disclosed and in many instances is accessible by only few employees with a special security clearance. This represents a challenge for both industry and research entities, as they face difficulties to comply with the necessary RD&D capabilities. To tackle some of the above mentioned challenges, the work in this thesis proposes a framework that will provide a holistic approach to generating a realistic synthetic grid. To ensure a feasible grid operation and realistic system design, various power system planning (PSP) methods, often used by planning engineers, are defined. The approach to sourcing data from various sources is also introduced and summarized. At first, distribution PSP is discussed and elaborated with the introduction of novel mathematical optimization models for radial, ring and slightly meshed distribution system respectively. The work further discusses and introduces the concepts of transmission PSP. Two different TSP models are defined as a DC power flow TSP approach and a conic AC power flow relaxation approach for the TSP problem. Furthermore, a detailed comparison and the strengths and differences of each of these models is presented and discussed. As part of the TSP, it is also essential to consider the security requirements imposed by the system regulators for system stability and an uninterrupted power supply. To address the security criteria requirements, a novel N-1 transmission system expansion planning model definition is proposed. A case study of the application of the proposed framework is defined for the development of a synthetic grid of the Singaporean power system. The available data and sources are discussed and the system structure is explained. The approach to developing the synthetic Singaporean grid is a bottom-up approach which considers the end user demand being allocated to adequate distribution systems. Once the distribution system is defined using the proposed distribution PSP methodology, the framework continues to model the sub-transmission and transmission networks to the highest voltage level. To demonstrate the usefulness of the proposed framework, the developed grid is used for the study and analysis of the viability and application of a novel distribution network expansion planning with Li-ion BESS. A hybrid optimization approach using a genetic algorithm (GA) and a mixed integer quadratically constrained programming (MIQCP) is defined. The GA determines the selection of new lines combined with the placement of the BESS, which are then used in the MIQCP sub-optimization to provide the optimal BESS sizing and test the power flow feasibility. To demonstrate the key benefits of the proposed method, the model is tested on the Singaporean synthetic grid model. The results are analyzed to conclude the benefits of combining new lines and BESS as an approach for a feasible cost effective distribution system expansion planning solution.